Pengaruh Aplikasi BBC Learning English terhadap Keterampilan Menulis (Writing Skill) dan Hasil Belajar Siswa SMA Plus Bustanul Ulum Jember - Sya’diyah, Halimatus; Kustiyowati, Kustiyowati; Silalahi, Amin (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This research employs a quantitative causal (cause and effect) method with variables including the BBC Learning English Android-based application as variable X, while Writing Skill as variable Y1, and Learning Outcomes as variable Y2. The research questions are as follows: 1) Does the Use of the BBC Learning English Android-based Application Influence the Writing Skills of Grade X Students at SMA Plus Bustanul Ulum Jember? 2) Does the Use of the BBC Learning English Android-based Application Influence the Learning Outcomes of Grade X Students at SMA Plus Bustanul Ulum Jember? 3) Does the Use of the BBC Learning English Android-based Application Influence Writing Skills and Learning Outcomes Simultaneously for Grade X Students at SMA Plus Bustanul Ulum Jember? The respondents of this research are Grade X students at SMA Plus Bustanul Ulum Jember. Data analysis employs multiple correlations using SPSS v. 23 for Windows. Data collection procedures include interviews, questionnaires, and documentation. The research findings can be summarized as follows: 1) The Hypothesis Test Result indicates a significant difference between the conventional learning media and the BBC Learning English Android-based application concerning the Writing Skills of Grade X students at SMA Plus Bustanul Ulum Jember. With a probability of 0.008 (sig) < 0.05, the null hypothesis is rejected. 2) The Hypothesis Test Result reveals that the use of the BBC Learning English Android-based application has a positive influence on the learning outcomes of students, as the analysis yields 0.535, signifying a 53.5% positive impact. This implies that the use of the BBC Learning English Android-based application affects students' learning outcomes. 3) The Hypothesis Test Result on the simultaneous influence of the BBC Learning English Android-based application on Writing Skills and learning outcomes indicates that the proposed hypothesis in Chapter II is accepted, signifying